2015
DOI: 10.1192/bjp.bp.113.143610
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stroke among patients with post-traumatic stress disorder: nationwide longitudinal study

Abstract: Individuals with PTSD have an increased risk of developing any stroke and ischaemic stroke. Further studies are required to investigate the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 30 publications
2
60
0
Order By: Relevance
“…Although investigators have examined posttraumatic stress disorder in relation to a range of health outcomes (including rheumatoid arthritis, stroke, heart disease, and cancer), some of the strongest empirical research, in terms of methodology and findings, has been with cardiometabolic diseases. 70,71 Numerous methodologically rigorous prospective population-based observational studies have found that posttraumatic stress disorder is associated with increased risk of incident CVD [72][73][74][75][76][77][78][79][80][81][82][83][84] and T2DM. [85][86][87] However, whether and how much of the relation between childhood adversity and cardiometabolic disease may be explained by posttraumatic stress disorder is unclear, especially because these studies have included traumatic events over the life course, with a substantial proportion of studies focused on veterans and military service-related trauma, not just adversity during childhood.…”
Section: Mental Health Factorsmentioning
confidence: 99%
“…Although investigators have examined posttraumatic stress disorder in relation to a range of health outcomes (including rheumatoid arthritis, stroke, heart disease, and cancer), some of the strongest empirical research, in terms of methodology and findings, has been with cardiometabolic diseases. 70,71 Numerous methodologically rigorous prospective population-based observational studies have found that posttraumatic stress disorder is associated with increased risk of incident CVD [72][73][74][75][76][77][78][79][80][81][82][83][84] and T2DM. [85][86][87] However, whether and how much of the relation between childhood adversity and cardiometabolic disease may be explained by posttraumatic stress disorder is unclear, especially because these studies have included traumatic events over the life course, with a substantial proportion of studies focused on veterans and military service-related trauma, not just adversity during childhood.…”
Section: Mental Health Factorsmentioning
confidence: 99%
“…While investigators have examined PTSD in relation to a range of health outcomes (including rheumatoid arthritis, stroke, heart disease, and cancer), some of the strongest empirical research—in terms of methodology and findings—has been with cardiometabolic diseases (Lohr et al , 2015). Numerous methodologically rigorous prospective population-based observational studies have found PTSD is associated with increased risk of incident cardiovascular disease (CVD) (Beristianos et al , 2014, Boscarino, 2006, 2008, Boscarino and Chang, 1999, Chen et al , 2015, Gradus et al , 2015, Jordan et al , 2011, Kubzansky et al , 2009, Kubzansky et al , 2007, Roy et al , 2015, Scherrer et al , 2010, Sumner et al , 2015, Vaccarino et al , 2013) and type 2 diabetes (T2D) (Boyko et al , 2010, Roberts et al , 2015, Vaccarino et al , 2014), even after adjusting for depression (see Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Among 5,217 participants in the Taiwan National Health Insurance Research Database, Chen et al found that PTSD was associated with a greater than 3-fold risk of developing stroke (22). We did not find that the magnitude of the association between PTSD and stroke differed significantly by race.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors, in turn, may predispose those with PTSD to a greater risk of developing chronic disease. Past research has demonstrated associations between PTSD and hypertension (1215), obesity (1620), metabolic disease (21), stroke (22) and type 2 diabetes (2325). A prospective association between PTSD and incident heart disease has been well-established (2630).…”
Section: Introductionmentioning
confidence: 99%